Unsolved mysteries: How does lipid peroxidation cause ferroptosis? - Feng, Huizhong (PLoS Biol, 2018)
Ferroptosis is a cell death process driven by damage to cell membranes and linked to numerous human diseases. Ferroptosis is caused by loss of activity of the key enzyme that is tasked with repairing oxidative damage to cell membranes—glutathione peroxidase 4 (GPX4). GPX4 normally removes the dangerous products of iron-dependent lipid peroxidation, protecting cell membranes from this type of damage; when GPX4 fails, ferroptosis ensues. Ferroptosis is distinct from apoptosis, necroptosis, necrosis, and other modes of cell death. Several key mysteries regarding how cells die during ferroptosis remain unsolved. First, the drivers of lipid peroxidation are not yet clear. Second, the subcellular location of lethal lipid peroxides remains an outstanding question. Finally, how exactly lipid peroxidation leads to cell death is an unsolved mystery. Answers to these questions will provide insights into the mechanisms of ferroptotic cell death and associated human diseases, as well as new therapeutic strategies for such diseases.